THE EFFECT OF INSECTICIDE-TREATED-NETS AND SLEEPING PLACE ON MALARIA PREVALENCE IN SCHOOL CHILDREN, ELSSOKI TOWN, SUDAN - Abdelsafi A Gabbad; Boraie A Elbashier; Mohammed A Elawad (European Scientific Journal, ESJ, 2014)
A survey was carried out in Elssoki town, central Sudan to investigate the effect of insecticide-treated nets (ITNs) and sleeping place on prevalence of malaria in primary school children. Using multi-stage sample technique, 394 children involved in the study. Blood samples were collected, prepared and examined by microscope. Other relevant data were obtained from children and their parents. The prevalence of malaria was 10%. Strong statistical significance was revealed between malaria prevalence and use of insecticide-treated nets (Relative risk = 7.76, 95% Confidence interval= 5.64 - 10.68) as well as outdoor sleeping (Relative risk = 18.6, 95% Confidence Interval (CI) = 10.9-31.7). Usage of insecticide-treated nets (ITNs) either outdoor or indoor might give a considerable reduction of malaria infection rate.